Hythlodaeus' Second Marathon Sentence of 926 Words and the "Contextual Launch" of the Utopia - Malsbary, Gerald (2021)
This article is a follow-up to a previous one in Moreana 51 (2014), which provided a detailed analysis of the immediately preceding 464-word sentence. The two sentences placed near the end of Utopia I work together to illustrate the political wisdom (in both domestic and foreign affairs) which the fictional Hythlodaeus has acquired in his travels, and at the same time encourage readers of Utopia to look forward to, and to accept the wisdom of the Utopians way of life as a positive model for Europe. There is an undoubted harmony between the sensible practices of the "Achorians" and "Macarians" and More's political philosophy as revealed in his epigrams. Nevertheless, the two long sentences also function as praeambula to the full-length account of the Utopians, and they are meant to guide our interpretation. The details of their structure, here analyzed, bring about certain rhetorical effects. In a crescendo of irony, the long sentences establish a rather peculiar character for Hythlodaeus as the sole narrator of Utopia II: he is an independent, utterly frank witness to this fictional "reality" of More's creation, and by the end of Utopia I we readers are prepared to listen to Utopia II with very critical ears indee.
Cet article suivre un autre antérieur (Moreana 51, 2014), qui fournit une analyse detaillée de la 464-mot phrase immédiatement precedent. Les deux phrases, situées au près du fin du Utopie I, cooperant a produire une illustration de la sagesse politique (des affaires et domestiques et étrangers) que Raphael Hythlodaeus avait acquiris dans ses voyages, et à la fois encouragent les auditeurs à faire un accueil favorable des moeurs Utopiennes, que sont sur le point d' apprendre, comme si convenables a les nations de l'Europe. L'harmonie entre les usages des "Achoriennes" et le "Macariennes" et la philosophie politique de Thomas More dans ses epigrammes est eclaircée. Néanmoins, les deux longues phrases se conduisent comme praeambula au portrait en pied des Utopiennes dans le second livre, et dirigent nôtre interpretation: les detailles de leur structure, ici analysées, produisent certains effets rhétoriques. Par un crescendo d'ironie, la personalité de Hythlodaeus, comme seul narrateur, devient temoin extraordinaire, avec parrhesia, de la creation littéraire de More; au fin de la Utopia I, nous auditeurs sommes prêtes à l' écouter la Utopie II ‘avec les oreilles très critiquées’.
Keywords: Connection between Utopia I and II; Hythlodaeus' rhetorical persona; Interpretation of Utopia; L' interpretation de l' Utopie; L'Utopie et les Epigrammes de More; La persona rhétorique de l'Hythlodaeus; Latin style of More; Le style Latine de Thomas More; Les phrases ‘marathoniques’ dans le fin de l'Utopie I; Les rapports entre Utopie I et II; Marathon sentences; Utopia and the epigrams of More